Did Ms Wisdom of Proverbs 8 become a mystery in 4QInstruction? - Venter, Pieter M. (HTS teologiese studies, 2016)
The Hebrew Bible is quoted and alluded to in 4QInstruction. There is an obvious similarity between the way the raz nihyeh of 4QInstruction and Lady Wisdom in Proverbs 8 function. This intertextual study investigates this phenomenon by comparing 4Q416 2 III 8–21 and 4Q417 1 I with Proverbs 8:12–21 and 8:22–31. It is concluded that apocalyptic influence changed the character of Lady Wisdom but not her essential function.